(3GdhLjR aj GdOQGSGJ GdeUQajI h GdJLGQjI (B/s - (3GdTQJhfj, ejTGd HjGQs; (3GdjGS, CHh YHjO s ((3HjQhJ(B: s (3GdeDSSI GdMOjKI ddcJGH(B, s, 2010)
(3YbO GdGjLGQ GdJehjdj h JWhjQ GdShb GdeGdjI h GdYbhO GdEFJeGfjI , JfXje egfI GdhSGWI GdeGdjI h GdCUhd GdhGLH EJHGYgG YfO abOGf MjGRI GdCSge h SfOGJ GdOjf h GdbSGFe h ZjQgG ef Gdbje GdefbhdI dMGedg , GdCSge h SfOGJ GdOjf GdJj JUOQgG GdTQcGJ GdeZadI h GdSfOGJ GdbGHdI GdJMhd Gdi CSge h CSge GdeUGQa GddHfGfjI , GdeUGQa GdeJNUUI , JSfjO GdehLhOGJ , bQhV GdOYe h SfOGJ GdOjf GdeQDhSI ecGaMI JHjjV GdGehGd , TgGOI GdGjOGY GdYehejI h GdeUQajI h gjFGJ GdGSJKeGQ GdLeGYj HGdbje GdefbhdI h SGFQ GdCOhGJ GdeGdjI , GdeUGQa GdGSdGejI aj dHfGf h HhQUI HjQhJ eY hLhO fUhU bGfhfjI eUQajIs
Keywords: (3GdCSges; (3GdHfhcs; (3GdHhQUGJs; (3GdJLGQIs